Pinna keloids: any role of complete surgical excision as monotherapy? - Warwantkar, Unmesh V.; Chandan, Shubhangi R. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Keloid is abnormal growth of scar tissue at the site of injury. External ear is one of the most common sites for keloids and most common reason being ear piercing. Many different treatment modalities such as surgery, intralesional steroids/ 5-FU, radiotherapy, silicone gel, cryotherapy, pressure earrings have been used for pinna keloids. Most of the studies suggest combination therapy of surgery and one of the above modalities gives better result and reduced recurrence compared to only surgery as monotherapy. At our institute we operated on 11 patients with 14 pinna keloids developed post ear piercing with aim not to leave behind any residue. None of the patients received any adjuvant therapy immediate post-surgery. Patients were followed up for 1 year. All the patients had good wound healing and acceptable scar post-surgery. Only 3 keloids out of 14 showed signs of recurrence and were treated with intralesional steroids. From this case series we would like to suggest complete surgical excision as primary mode of treatment (monotherapy) for pinna keloids developed post ear piercing without risk of recurrence and adjuvant therapy like intralesional steroids can be started at the onset of recurrence and not generally.